The Impact of Anti-Drug Soft Skills Training on the Competence and Performance of Guidance and Counseling Teachers in Indonesia - Fadiyanto, Guruh Achmad; Rizal, Afib (Universitas Negeri Makassar, 2025)
This study aims to describe and analyze the factors influencing the Competence and Performance of BK Teachers after the Anti-Drug Soft Skills training. The census was conducted on 517 (76%) participants throughout Indonesia in 2024. The research instruments were questionnaires (quantitative data), pretests, post-test results, action plan forms, and relevant literature reviews (qualitative data). Data collection was carried out online with inferential statistical analysis using SmartPLS 3.2.9. The study results prove that the age of BK Teachers participating in Training is between 22-60 years, the length of service is relatively new, the Number of Training attended is tiny, and cosmopolitanism is in the Medium category (having a sufficient willingness to innovate). Other variables are in the high category. This data means that participants are delighted with the implementation of the training, that institutional support (schools) is excellent, and that competence and performance are also excellent. The variables of Individual Characteristics and Institutional Support have a positive effect on Competence. The Competence variable also has a positive effect on Performance. So, institutional support and individual characteristics affect Competence, and Competence affects Teacher Performance.